The Role of Big Data in Administrative Decision-Making - Aria Mulyapradana (Penelitian dan Pengembangan Ilmu, 2024)
The use of Big Data in the context of administrative decision making has become the main focus of research in efforts to improve the quality of public services. This research aims to investigate how Big Data affects the quality of public services and explore its implications. The research methodology includes literature analysis as well as relevant case studies to identify trends and impacts of Big Data use. The results show that the use of Big Data can increase the responsiveness, effectiveness and efficiency of administrative decision making in public services. However, challenges related to data privacy and technical complexity still need to be overcome. The implications of this research highlight the importance of adopting Big Data technology in improving the quality of public services, while recognizing the need for ethical and technical considerations in its implementation.